PERSEPSI MASYARAKAT TERHADAP HUTAN PRODUKSI DI KENAGARIAN SUNGAI KUNYIT KECAMATAN SANGIR BALAI JANGGO KABUPATEN SOLOK SELATAN - Fanny Prina Putri; Surtani Surtani (DEPARTEMEN GEOGRAFI FIS UNP, 2021)
The objectives of this study were (1) Public perception of production forests to convert forest into agricultural land, (2) Field supervision by the authorities, (3) Utilization of production forests. This type of research is qualitative research. The data used are primary data. Primary data was obtained from direct interviews with the Nagari Sungai Kunyit community. Data collection techniques using observation, interview, and documentation techniques. Data analysis techniques by performing data reduction, data presentation, and drawing conclusions. The results of this study are: (1) The community's perception of forest conversion still considers the forest as a livelihood, beneficial for their economic resources and thinks that the forest is their right and a gift to be used at will. (2) The public perception of production forests regarding field supervision by authorized parties shows that the community does not understand about forest management and conservation, because on-the-ground supervision by authorized parties is rarely carried out or not implemented. (3) The community's perception of utilization of production forests, the community feels lucky with the existence of production forests, seen from the actions they take by clearing agricultural or agricultural land to meet their income and daily needs.